First record of the genus Rhopaltriplasia Diakonoff from China, with description of two new species (Lepidoptera: Tortricidae: Olethreutinae) - Yu, Hai Li; Li, Hou Hun (Zootaxa, 2005)
Rhopaltriplasia Diakonoff, 1973 is reported from China for the first time. Rhopaltriplasia rotundipetalina sp. nov. and Rhopaltriplasia spinalis sp. nov. are described and illustrated. Rhopaltriplasia insignata Kuznetsov is recorded for the first time from this country. A key for identification of the Chinese species is given.